The Adab (Manners) of Tawadhu' in Social Interaction from the Perspective of Tafsir Ibn Kathir (Analysis of Surah Luqman Verses 18-19) - Maqfiroh, Hanifah Aulia Amalia; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
This study focuses on the concept of Adab Tawadhu' in social interaction from the perspective of Tafsir Ibnu Katsir, especially in the context of Surah Luqman verses 18-19. This study uses a descriptive qualitative method with the main data in the form of Tafsir Ibnu Katsir and Surah Luqman verses 18-19. The analysis was carried out through literature study and content analysis. This study aims to understand more deeply how adab tawadhu can be applied in social interaction and how it can positively impact building harmonious and mutually respectful relationships in society. From this study, it can be concluded that the adab tawadhu' has an important role in social interaction. From the perspective of Tafsir Ibn Kathir, the adab tawadhu is not only about being humble but also about how someone treats others with respect and justice. Implementing the adab tawadhu' in social interaction can help build harmonious and respectful social relationships. Therefore, we must understand and apply the adab tawadhu' in everyday life.